Innovation in Large and Small Firms - Kenneth J. Arrow (Journal of Small Business Finance, 1993)
This essay is intended to begin the elaboration of a theme: the interaction between the observed sizes of firms and their internal decision making procedures. This theme is a major one in the symphony of entrepreneurial activity. The entrepreneur, as the maker and changer of economic and productive life, is usually envisaged as an individual. In the neoclassical tradition, he (or, rarely, she) is the lightning calculator, the individual who rapidly scans the field of alternative productive processes and chooses the optimum any given set of prices.
Keywords: O31; L25; M13; 650; Small Firm; Small Business; Innovation